ASSESSMENT OF HEALTH PROBLEMS DURING MENSTRUATION AMONG RURAL ADOLESCENT GIRLS WITH REFERENCE TO RURAL AREA OF PUPRI ZONE OF SITAMARHI DISTRICT - Neha Kumari; Kusum Kumari; Vidisha Mishra; Shweta Priyadarshini; Sangeeta Rani; Renu Kumari (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The world's culture and civilization have originated in villages, no matter where those villages are, America, Africa, Asia or any continent. Our poets have also tried to realize the idea of ​​a heaven on earth by expressing expressions like 'Aha! What is village life' or 'Bharat Mata Gram Vasini', but the reality of our today is that whatever may have been said in all the claims of development, our villages are still seen as backward lives. The menstrual hygiene practices of adolescent girls in rural areas are still influenced by social taboos and beliefs. Thus, it has become an obstacle to the objective of Swachh Bharat Mission, as well as a major producer of various vaginal diseases. 40 rural adolescent girls belonging to Pupri zone of Sitamarhi district (Bihar) were interviewed and the data was analyzed through statistical tools. Most of the girls had little knowledge about ideal MHM practices. Their technique of disposal of used sanitary pads was not environmental friendly. They pointed out the dire need of menstrual hygiene training programs in rural areas.